Neutron Reflectivity and Performance of Polyamide Nanofilms for Water Desalination - Foglia,F; Karan,S; Nania,M; Jiang,Z; Porter,AE; Barker,R; Livingston,AG; Cabral,JT (ADVANCED FUNCTIONAL MATERIALS, 2017)
The structure and hydration of polyamide (PA) membranes are investigated with a combination of neutron and X-ray reflectivity, and their performance is benchmarked in reverse osmosis water desalination. PA membranes are synthesized by the interfacial polymerization of m-phenylenediamine (MPD) and trimesoyl chloride (TMC), varying systematically reaction time, concentration, and stoichiometry, to yield large-area exceptionally planar films of ≈10 nm thickness. Reflectivity is employed to precisely determine membrane thickness and roughness, as well as the (TMC/MPD) concentration profile, and response to hydration in the vapor phase. PA film thickness is found to increase linearly with reaction time, albeit with a nonzero intercept, and the composition cross-sectional profile is found to be uniform, at the conditions investigated. Vapor hydration with H2O and D2O from 0 to 100% relative humidity results in considerable swelling (up to 20%), but also yields uniform cross-sectional profiles. The resulting film thickness is found to be predominantly set by the MPD concentration, while TMC regulates water uptake. A favorable correlation is found between higher swelling and water uptake with permeance. The data provide quantitative insight into the film formation mechanisms and correlate reaction conditions, cross-sectional nanostructure, and performance of the PA active layer in RO membranes for desalination.